Health psychology - Taylor, Shelley E. (McGraw - Hill, 2003)
Health psychology ia a science, and consequently it is important to com-municate not only the research itself but also some understanding of how studies were disigned and why they were designed that way . Important studies are described in-depth, so that the student may have a sense of the methods researchers use to make decisions about how to gather the best data on a problem or how to intervene most effectively.